A rapid national survey of terrestrial and semi-aquatic mammals using environmental DNA metabarcoding - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Robert Raynor; Claire Howe; Naiara Guimarães Sales; Allan D. McDevitt (Mammalian Biology, 2026)
Assessing the distribution and diversity of terrestrial and semi-aquatic mammals is fundamental for effective conservation efforts. Environmental DNA (eDNA) metabarcoding has emerged as a rapid and cost-effective method for surveying mammals. It has promising avenues for conducting national surveys and enabling comprehensive assessments of mammalian populations across diverse habitats. We collected eDNA samples from 60 water systems across six regions in England (from north to south), United Kingdom, over a period of up to four days in each region. We detected 26 mammals from five taxonomic orders across all sampling locations, recovering 53–89% of the known mammal community in each region. Our findings underscore the feasibility of utilising eDNA metabarcoding for rapidly surveying mammal populations on a national scale, potentially complementing data from existing surveys/records or implementing in data deficient regions. However, challenges remain for surveying certain species using this method, with varying levels of detectability of key species (e.g. otters) across regions.

The role of ocean circulation and regolith removal in triggering the Mid-Pleistocene Transition: Insights from authigenic Nd isotopes - Thomas J. Williams; Alexander M. Piotrowski; Jacob N.W. Howe; Claus-Dieter Hillenbrand; Claire S. Allen; Josephine A. Clegg (Quaternary Science Reviews, 2024)

Mining-related environmental disasters: A High Reliability Organisation (HRO) perspective - Layla Howe; Susan Johnston; Claire Côte (Journal of Cleaner Production, 2023)